Rotating machinery vibration : from analysis to troubleshooting. - Adams, Maurice L., Jr., ....- (Boca Raton : CRC, 2010)
Table of Contents Pt. 1 Primer on Rotor Vibration 1 Vibration Concepts and Methods 2 Lateral Rotor Vibration Analysis Models 3 Torsional Rotor Vibration Analysis Models Pt. 2 Rotor Dynamic Analyses 4 RDA Code for Lateral Rotor Vibration Analyses 5 Bearing and Seal Rotor Dynamics 6 Turbomachinery Impeller and Blade Effects Pt. 3 Monitoring and Diagnostics 7 Rotor Vibration Measurement and Acquisition 8 Vibration Severity Guidelines 9 Signal Analysis and Identification of Vibration Causes Pt. 4 Troubleshooting Case Studies 10 Rotor Unbalance and Critical Speed Case Studies 11 Self-Excited Rotor Vibration Case Studies 12 Additional Rotor Vibration Problem Cases and Topics